Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1002/pssb.2221650231
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Electronic Polarizabilities in Ionic Crystals

Abstract: The existing sets of additive electronic polarizabilities for alkali halides and alkaline earth chalcogenides are examined by evaluating the high frequency electronic dielectric constants and presenting a comparison with experimental data. The crystalline state values of polarizabilities are also compared with free ion values. Various physical effects responsible for changing the values of polarizabilities in the crystalline state are discussed. The differences in free state and crystalline state polarizabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…A quantitative measure of cation-anion interaction is given by the so-called interionic interaction parameter A, which represents the charge overlapping of the negative ion with its nearest positive neighbor for a chosen cation-anion pair. 27,33 In the case of oxides, the parameter A correlates with a reduction in the polarizability of oxide ion when placed in oxide glass network with respect to the free ion polarizability due to interaction inside. The interionic interaction parameter, therefore, means the degree of the overlapping between O2p and cation valence orbitals in oxides, indicating the chemical bond strength of cation-oxide ion pairs.…”
Section: Polarizabilit Y and Interionic Interaction Parameter Of Simpmentioning
confidence: 99%
“…A quantitative measure of cation-anion interaction is given by the so-called interionic interaction parameter A, which represents the charge overlapping of the negative ion with its nearest positive neighbor for a chosen cation-anion pair. 27,33 In the case of oxides, the parameter A correlates with a reduction in the polarizability of oxide ion when placed in oxide glass network with respect to the free ion polarizability due to interaction inside. The interionic interaction parameter, therefore, means the degree of the overlapping between O2p and cation valence orbitals in oxides, indicating the chemical bond strength of cation-oxide ion pairs.…”
Section: Polarizabilit Y and Interionic Interaction Parameter Of Simpmentioning
confidence: 99%
“…Recently Dimitrov and Komatsu4) have evaluated the values of parameter A for numerous simple oxides based on the approach deve loped in Ref. 3). It was found that in the case of simple oxides the parameter A represents the interionic interac tion between 2p-electron cloud of the oxide ion and the valence cloud of the cation in respect to form a chemical bond.…”
Section: Introductionmentioning
confidence: 99%
“…It correlates with reducing the polarizability of negative ion placed in a crystal lattice in respect to the free-ion polarizability. Dikshit and Kumar based on the theory proposed by Yamashita and Kurosawa derived an expression for the calculation of the interaction parameter A for a given cation-anion pair [41] …”
Section: Interaction Parametermentioning
confidence: 99%